Pengaruh Struktur Organisasi dan Pengawasan terhadap Kepuasan Kerja Kepala Sekolah pada SMA Swasta di Kabupaten Bogor - Subaiki Ikhwan (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2017)
This study aims to determine the influence of organizational structure and controlling to job satisfaction in Senior High School of District Bogor. This research uses causal path analysis. Technique of data collecting is using the instrument form questionnaire. This instrument is calibrated with the test item, validity and reliability coefficients. The number of 62 head master’s as sample was selected by proportional random sampling. The result of this research indicated that, 1) There is a direct influence of organizational structure toward the job satisfaction, 2) There is a direct influence of controlling toward the job satisfaction, 3) There is a direct influence of organizational structure toward the controling. The implication of this research is an effort in improving the job satisfaction of SMA Headmaster shall be considered through organizational structure and controlling.